Design and development of a mock circulation loop for blood pumps - Ou, Jianwen. (2009)
Congestive heart failure is a condition where insufficient blood is circulated around the body resulting in poor perfusion and multiple organ failure. Just in America alone, heart failure accounts for approximately 250,000 deaths yearly. With the limited number of hearts available for transplant, patients must seek other alternative. However with the use of left ventricular assist device (LVAD), the patients’ life quality will improve. However before a LVAD can be implanted, they must first be tested in an experimental flow loop. These mock circulatory loop are use to set the standard for testing pump while varying the different hemodynamic parameters.